Implications Learning Differentiate Regarding Student Learning Outcomes in Social Sciences Subjects Class IV SDN 2 Bahonsuai Bumi Raya District , Regency Morowali - Nurasia; Hasan; Idrus (Kirana Publisher (KNPub), 2024)
Education is very important capital in development a country of use obtain source Power quality human being , because through arrangement good education​ will produce good graduates too . As for the formula the author 's problem apply is is there influence Learning Differentiate Regarding Learning Outcomes Students in Social Sciences Subjects Students Class IV SDN 2 Bahonsuai . Research objectives In conducting study this , writer own desired goal​ achieved , ie analyze influence learning differentiate to results Study student class IV at SDN 2 Bahonsuai . Study This is type study quantitative . Study quantitative can interpreted as method research based on philosophy​ positivism , used For research on populations or sample specific , data collection . Test instrument study used For know how much big level validity , reliability , level difficulty , and power differentiator question . Before examine the average similarity second class with use analysis independent sample t-test, then Normality tests , homogeneity tests are needed , especially formerly . After normality test , homogeneity test , on second class , then the data has fulfil For carry out hypothesis testing . test results​ reliability carried out in a way whole use Cronbach's alpha technique with SPSS version 22 assistance , obtained results that index correlation of 20 items question of 0.937 so level its reliability categorized as very high .